The Analysis of Thrust and Efficiency of B – Series Propeller : Influence of Speed Variation - Aldyn Clinton Partahi Oloan; Muswar Muslim; Ayom Buwono (Institut Teknologi Sepuluh Nopember, 2023)
For variations in ship speed given data such as length perpendicular (LPP) 28 meters, propeller rotation (N) 290 rpm and shaft horse power (SHP) of 452.5 Hp by setting speed values varying from 4 knots to 9 knots, the average propeller efficiency for the B4-40 type is 60% while the average trust or thrust of the ship is 5873.5 kg and the average trust coefficient is 0.28. Likewise for the B4-55 type, the average propeller efficiency is around 58.6%, then the average thrust for the ship is 5736.3 kg and the thrust coefficient for the ship is 6.6.